2018
DOI: 10.1111/vop.12555
|View full text |Cite
|
Sign up to set email alerts
|

Technique, postoperative complications, and visual outcomes of phacoemulsification cataract surgery in 21 penguins (27 eyes): 2011‐2015

Abstract: The prognosis for vision and behavioral improvement after phacoemulsification surgery in penguins is good, with low incidence of vision-threatening complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Modern veterinary medicine can mostly successfully treat a cataract. Also, there are cases of successful treatment in penguins reported [5], although there are not many studies and case reports in that specific field so far.…”
Section: Pathological Findingsmentioning
confidence: 99%
“…Modern veterinary medicine can mostly successfully treat a cataract. Also, there are cases of successful treatment in penguins reported [5], although there are not many studies and case reports in that specific field so far.…”
Section: Pathological Findingsmentioning
confidence: 99%
“…A recent study from North American zoos revealed that cataract is a prominent finding in aged penguins 31 and cataract surgery in penguins was shown to be successful and contributed to the welfare of captive penguins 16,35 . In order to minimize duration of anesthesia, no pre‐operative ERG was recorded in the 21 birds operated by Church et al 16 . However, our study shows that such recordings are feasible and diagnostic in alert birds even without dark adaptation or pupil dilation.…”
Section: Discussionmentioning
confidence: 71%
“…Pupils were not dilated as the iris muscles in penguins are mostly striated and are unresponsive to parasympatholytic mydriatic drugs 15 . The only publication we have found reporting pharmacological mydriasis in penguins involved intracameral injection of a muscle relaxant, 16 which was not justifiable for the purpose of this study. While other protocols for achieving mydriasis using muscle relaxants in various avian species have been published, some require application of multiple drops at 15 min intervals 16,17 ; dangerous side effects have been reported 17 and their use would have required repeated capturing of the birds and unacceptable stress.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations